Statistics for psychology - Arthur, Aron; Coups, Elliot J.;Aron, Elaine N. (Boston, Massachusetts : Pearson, 2013)
The heart of this book was written over summer in a small apartment near the Place Saint Ferdinand, having been outlines in nearby cafes and on walks in the Bois de Boulogne. It is based on our collective experience of many decades of teaching, researching, and writing. We believe that the result is a book as different from the conventional lot of statistics texts as Paris is from Patagonia, yet still somfortable and stimulating to the long-suffering sommunity of statistics instructions.
Chapter 1 : Displaying the order in am group of numbers using tables and graphs -- Chapter 2 : Central tendency and variability -- Chapter 3 : Some key ingredients for inferential statistics -- Chapter 4 : Introduction to hypothesis testing -- Chapter 5 : Hypothesis tests with means of samples -- Chapter 6 : Making sense of statistical significance : decisions errors, effect, size, and statistical power -- Chapter 7 : Introduction to t tests : single sample and dependent means -- Chapter 8 : The t Test for independent means -- Chapter 9 : Introduction to analysis of variance -- Chapter 10 : Factorial analysis of variance -- Chapter 11 : Correlation -- Chapter 12 : Prediction -- Chapter 13 : Chi-square tests -- Chapter 14 : Strategies when population distributions are not normal : data transformation s and rank-order tests -- Chapter 15 : The General linear model and making sense of advanced statistical procedures in research articles.
Includes bibliographical references and index.
Keywords: PSYCHOLOGY